2021
DOI: 10.2147/idr.s293583
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Multidrug Resistant Tuberculosis Treatment and Case Management in Chongqing, China – A Mixed Method Research Study

Abstract: This paper evaluated the treatment adherence for multidrug-resistant tuberculosis (MDR-TB) and MDR-TB case management (MTCM) in Chongqing, China in order to identify factors associated with poor treatment adherence and case management. Methods: Surveys with 132 MDR-TB patients and six in-depth interviews with health care workers (HCWs) from primary health centers (PHC), doctors from MDR-TB designated hospitals and MDR-TB patients were conducted. Surveys collected demographic and socioeconomic characteristics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 23 publications
0
27
1
6
Order By: Relevance
“…We found that almost 20% of DS-TB patients had missed doses, which occurred most frequently, followed by a lack of follow-up sputum examination and interrupted treatment. The incidence of poor adherence was much higher in a previous study on MDR-TB patients in Chongqing [34] but lower than that in DS-TB patients reported in a previous study [25].…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…We found that almost 20% of DS-TB patients had missed doses, which occurred most frequently, followed by a lack of follow-up sputum examination and interrupted treatment. The incidence of poor adherence was much higher in a previous study on MDR-TB patients in Chongqing [34] but lower than that in DS-TB patients reported in a previous study [25].…”
Section: Discussioncontrasting
confidence: 71%
“…Discontinuation of medication for two to eight consecutive weeks before restarting treatment [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study also reported drug side effects and conflicts with the timing of treatment services as the barriers to treatment adherence [ 19 ]. Another study found that poor adherence to DR-TB treatment is associated with negative side effects from the treatment, busy work schedules, and financial difficulties [ 8 ]. In patients with multidrug-resistant tuberculosis (MDR-TB), both patient and regimen were related factors associated with LTFU [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hasil review dari 1 artikel dengan 111 responden pada penelitian Wang et all (2019) pasien TB Multy Drug Resistant didapatkan data kepatuhan minum obat dengan metode pengukuran kepatuhan pill count hasil kepatuhan minum obat pada pasien TB MDR sebesar tidak patuh minum obat 105 (95%). Sejalan dengan penelitian yang dilakukan oleh Wei Xing et all (2021) [27] pasien yang pernah menerima pengobatan TB MDR tidak patuh pengobatan 80 (62,5%). Perlaku tidak patuh pada penelitian Wei Xing et all (2021) adalah perilaku ketidakpatuhan melewatkan satu dosis pengobatan, mengurangi asupan obat, melewatkan pemeriksaan dahak lanjutan yang disayaratkan oleh standar rejimen pengobatan, dan pengobatan yang terputus.…”
Section: B Kepatuhan Minum Obatunclassified